2016
DOI: 10.1016/j.jenvman.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil structure on contaminant leaching from injected slurry

Abstract: Animal manure application to agricultural land provides beneficial organic matter and nutrients but can spread harmful contaminants to the environment. Contamination of fresh produce, surface water and shallow groundwater with the manure-borne pollutants can be a critical concern. Leaching and persistence of nitrogen, microorganisms (bacteriophage, E. coli, and Enterococcus) and a group of steroid hormone (estrogens) were investigated after injection of swine slurry into either intact (structured) or disturbed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…Nahar et al (2006) reported that fresh manure loosened soil aggregates by increasing microbial activities more than the composted dry manure. The loose aggregates can facilitate soil water transport through its pore spaces (Amin et al, 2016). Manure application increased soil organic matter from 1.1 to 1.4-1.9% and electrical conductivity from 132 to 156-206 µS cm -1 but reduced bulk density from 1.33 to 1.25 g cm -3 in the topsoil.…”
Section: Resultsmentioning
confidence: 99%
“…Nahar et al (2006) reported that fresh manure loosened soil aggregates by increasing microbial activities more than the composted dry manure. The loose aggregates can facilitate soil water transport through its pore spaces (Amin et al, 2016). Manure application increased soil organic matter from 1.1 to 1.4-1.9% and electrical conductivity from 132 to 156-206 µS cm -1 but reduced bulk density from 1.33 to 1.25 g cm -3 in the topsoil.…”
Section: Resultsmentioning
confidence: 99%
“…A aplicação da adubação por meio da utilização de fertilizantes orgânicos (esterco bovino e cama de aves) combinado com inorgânicos (NPK) proporcionou influência no melhor desenvolvimento vegetativo, no comprimento e na largura máxima da folha (Amin et al, 2016), que proporcionou área foliar (AF) e índice da área foliar (IAF) maiores na cultura do açafrão da terra.…”
Section: Número De Folhas Grandes Por Plantaunclassified
“…Altered soil hydraulic properties may affect the transport of nutrients and contaminants (Amin et al, 2016). Dislodged colloids during puddling can remarkably influence the transportation of sorbing pollutants in the vadose zone.…”
Section: Introductionmentioning
confidence: 99%